PENGARUH PENGETAHUAN TENTANG KOPERASI, KUALITAS LAYANAN, DAN MOTIVASI BERKOPERASI, TERHADAP MINAT MENJADI ANGGOTA KOPERASI MAHASISWA UNIVERSITAS KANJURUHAN MALANG - Khoridatul Hidayah; Lilik Sri Hariani; Riril Mardiana Firdaus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
Student Cooperation is a forum for cooperation learning and practice in the field. Whether or not a cooperative grows depends on how many students are interested in becoming a member of Kopma Unikama. This study uses ex-post-facto with multiple linear regression analysis. research on knowledge about cooperatives, service quality, cooperative motivation. The focus of research on students of economic education year 2012-2016 as many as 213 students, sampling technique propotional random sampling with the number of samples of 53 students. Result of hypothesis test by using F test analysis result of significant influence together knowledge about cooperatives, service quality and cooperative motivation, to interest to become member of Kopma Unikama. R squere shows R2 which means variable x1, x2, x3 able to give contribution equal to 58,6% to variable Y, rest 41,4% influenced by other factors. This research can develop and grow the soul to cooperate through student cooperatives and add insight, organizational experience and advance the Indonesian Cooperation.